Educar-se entre usuários/as de crack - Souza, Rosângela Pereira de (2015)
This research aimed at comprehending the educational processes developed in relations amongst crack users, at social practice of crack use on public spaces. In this context, education is taken as an intersubjective construction. The theoretical reference was based on the perspective of popular education, as well as the liberation philosophy. The methodology was based on dialogical investigation processes, from participative observation, interviews and field journal, through the living together of the other research subjects, supported by a qualitative approach. The field research it was conducted in the period February and August 2014, in a crack use area, know as Mata do Gueto, in Piracicaba-SP. The interview was conducted with a cooperator, crack user who had lived in this public area for a period of five years. In order to analyze the data the content analysis technique has been used, and that was done in steps: pre-analysis (exhaustive reading of data); material exploration (choosing categories of analysis) and treatment of results and data final analysis. This procedure yielded at the following categories: Mata do Gueto; The Crack Use; “Let's go to the ideas, the beast catches, is run”. The results showed that amongst crack users, they learn and teach: respect; good manners among people from Mata do Gueto; rules; caring attitude; problem solving and peace. The processes upon which the education happens in such a context become possible through speeches/dialogues/words, expressions, gestures, repetitive actions, shouting, apologies and violence. The participants say that the word is worth more than violence, as long as there is a dialogue. According to them, that is the most effective way of teaching and learning. In short, this research expects to contribute to the development of actions and public policy strategies, including the Harm Reduction and contribute with the humanized educational practices with and among crack users, as well as collaborate with the education that happens in environments non-school and school.